DOI: 10.18297/etd/1063
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of the relationships between the therapeutic alliance, empathy, and genuineness in individual adult psychotherapy.

Abstract: ACKNOWLEDGEMENTSI would like to thank my co-chairs for their individual contributions and guidance.Dr. Jesse Owen, thank you for your help exploring the many nuances in the therapeutic relationship literature and helping me apply this work to psychotherapy practice. Our talks helped me see the different facets of the therapeutic relationship and how perception means so much in therapy. I also want to thank you for your insight during advanced practicum and for introducing me to short-term dynamic therapy, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 152 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…The working alliance is commonly defined as the emotional bond established in the therapeutic dyad, and the agreement between the two about the goals of therapy and the tasks necessary to achieve them (Bordin, 1979; Hatcher and Barends, 2006). Meta-analyses have consistently demonstrated that stronger alliance is associated with better treatment outcome across treatment modalities, both in various psychotherapies (based on a data from more than 30,000 patients; Flückiger et al, 2018) and in psychopharmacotherapy ( N = 1,065 patients; Totura et al, 2017).…”
Section: The Roles Of the Working Alliance In Treatmentmentioning
confidence: 99%
“…The working alliance is commonly defined as the emotional bond established in the therapeutic dyad, and the agreement between the two about the goals of therapy and the tasks necessary to achieve them (Bordin, 1979; Hatcher and Barends, 2006). Meta-analyses have consistently demonstrated that stronger alliance is associated with better treatment outcome across treatment modalities, both in various psychotherapies (based on a data from more than 30,000 patients; Flückiger et al, 2018) and in psychopharmacotherapy ( N = 1,065 patients; Totura et al, 2017).…”
Section: The Roles Of the Working Alliance In Treatmentmentioning
confidence: 99%